The potential of circHIPK3 as a biomarker in chronic myeloid leukemia - Gomez, Eduardo Wandame; De Paula, Laura Berti; Weimer, Rafael Diogo; Hellwig, Alessandra Helena da Silva; Rodrigues, Grazielle Motta; Alegretti, Ana Paula; de Oliveira, Jarbas Rodrigues (Frontiers in Oncology, 2024)
Chronic myeloid leukemia (CML) is a myeloproliferative disorder characterized by leukocytosis and left shift. The primary molecular alteration is the BCR::ABL1, chimeric oncoprotein with tyrosine kinase activity, responsible for the initial oncogenesis of the disease. Therapy of CML was revolutionized with the advent of tyrosine kinase inhibitors, but it is still not considered curative and may present resistance and serious adverse effects. Discoveries in CML inaugurated a new era in cancer treatment and despite all the advances, a new biomarker is needed to detect resistance and adverse effects. Circular RNAs (circRNAs) are a special type of non-coding RNA formed through a process called backsplicing. The majority of circRNAs are derived from protein-coding genes. CircHIPK3 is formed from the second exon of the HIPK3 gene and has been found in various pathologies, including different types of cancer. New approaches have demonstrated the potential of circular RNAs in cancer research, and circHIPK3 has shown promising results. It is often associated with cellular regulatory pathways, suggesting an important role in the molecular dynamics of tumors. The identification of biomarkers is an important tool for therapeutic improvement; thus we review the role of circHIPK3 and its potential as a biomarker in CML.